The paradigm of fragmented sensitivity in Gorgias' 'PTMO' (Revista Archai, 2021)
The article aims to show the importance of Gorgias’ treatment of sensation and its relation to thought and language in the two preserved summaries of the Peri tou me ontos (PTMO). I argue that Gorgias postulates there a radical fragmentation of man in multiple sensations, as well as of the object in a multiplicity of edges that do not find any synthetic moment. The paradigm of fragmented sensitivity is the central scheme, unquestioned in the treatise, that will be projected to the relationships between being, thought and discourse to support the theses of the impossibility of knowledge and communication. Beyond Gorgias’ intentions, the article aims to exhibit the important projections of the aporias raised by him as shown in Plato and Aristotle's proposals regarding sensitivity.